DLin-MC3-Containing mRNA Lipid Nanoparticles Induce an Antibody Th2-Biased Immune Response Polarization in a Delivery Route-Dependent Manner in Mice - Altan Yavuz; Céline Coiffier; Cynthia Garapon; Serra Gurcan; Claire Monge; Jean-Yves Exposito; Danielle Campiol Arruda; Bernard Verrier (MDPI AG, 2023)
mRNA-based vaccines have made a leap forward since the SARS-CoV-2 pandemic and are currently used to develop anti-infectious therapies. If the selection of a delivery system and an optimized mRNA sequence are two key factors to reach in vivo efficacy, the optimal administration route for those vaccines remains unclear. We investigated the influence of lipid components and immunization route regarding the intensity and quality of humoral immune responses in mice. The immunogenicity of HIV-p55Gag encoded mRNA encapsulated into D-Lin-MC3-DMA or GenVoy-ionizable lipid-based LNPs was compared after intramuscular or subcutaneous routes. Three sequential mRNA vaccines were administrated followed by a heterologous boost composed of p24-HIV protein antigen. Despite equivalent IgG kinetic profiles of general humoral responses, IgG1/IgG2a ratio analysis showed a Th2/Th1 balance toward a Th1-biased cellular immune response when both LNPs were administrated via the intramuscular route. Surprisingly, a Th2-biased antibody immunity was observed when DLin-containing vaccine was injected subcutaneously. A protein-based vaccine boost appeared to reverse this balance to a cellular-biased response correlated to an increase in antibody avidity. Our finding suggests that the intrinsic adjuvant effect of ionizable lipids appears to be dependent on the delivery route used, which could be relevant to reach potent and long-lasting immunity after mRNA-based immunization.